When I grow up I'll be a librarian - Miller, Connie Colwell, 1976-; Baroncelli, Silvia (Mankato, MN : Amicus Illustrated/Amicus Ink, 2019)
Readers follow along on a day in the life of a librarian as a young girl pretends that the family den is a public library. Includes a glossary of library terms and a library scavenger hunt activity.
3.8
K-3
640L
Keywords: Librarians -- Juvenile literature; Library science; Librarians; Vocational guidance; Picture books -- Juvenile literature